Validation into Arabic versions of Dementia Rating Scales, Dementia Caregivers Scales, and Dementia Research Instruments - Georges Elie Karam; Mohannad Nawaf Khandakji; Nayri Sarkis Sahakian; Jessica Christian Dandan; Elie Georges Karam (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2018)
Abstract Introduction This study aimed to examine the validity and internal consistency of Arabic versions of the eight‐item Alzheimer's Dementia, Alzheimer Questionnaire, and Clinical Dementia Rating scales and to assess the Arabic version of Katz Activities of Daily Living, and Neuropsychiatric Inventory. Methods One hundred fifty participants were recruited from different settings; they underwent clinical interviews and filled the aforementioned scales. Results In our sample, 56.8% of the sample suffered from dementia. The Arabic eight‐item Alzheimer's Dementia had excellent psychometric properties, and the Arabic Alzheimer Questionnaire showed near‐perfect properties with sensitivity and specificity reaching 100%. In addition, the Arabic Clinical Dementia Rating (A‐CDR)–sum of boxes was superior to the regular A‐CDR score in detecting dementia cases among the study sample. The A‐CDR showed similar characteristics as the original version. The Katz scores demonstrated a strong negative correlation with eight‐item Alzheimer's Dementia scores. Conclusion Based on this study, health professionals now have reliable and validated tools to be used in clinical and research settings among Arabic‐speaking populations.